Symptoms of depression and quality of life of people living with HIV/AIDS Síntomas de depresión y calidad de vida de personas viviendo con HIV/Sida Sintomas de depressão e qualidade de vida de pessoas vivendo com HIV/aids - Renata Karina Reis; Vanderley José Haas; Claudia Benedita dos Santos; Sheila Araujo Teles; Marli Teresinha Gimenez Galvão; Elucir Gir (Universidade de São Paulo, 2011)
This is a cross-sectional study conducted with 228 people living with HIV/AIDS in a municipality in the State of São Paulo during 2007 and 2008. The aims of this study were to investigate the intensity of the depressive symptoms in individuals with HIV/AIDS treated at two referral units in Ribeirão Preto, Brazil, and to compare the quality of life with the different degrees of intensity of the depressive symptoms in these individuals, according to gender. Data were collected through individual interviews, using the Beck Depression Inventory and HIV/AIDS Targeted Quality of Life (HATQoL). A total of 63 (27.6%) patients with symptoms of depression (mild, moderate and severe) were detected. The women presented more severe symptoms of intensity of depression than men. Individuals with depressive symptoms presented lower scores of quality of life than individuals without these symptoms, with statistically significant differences between the means/medians in most domains of the HATQoL. Healthcare professionals should offer integral care for people with HIV/AIDS, emphasizing the depressive symptoms. Se trata de un estudio de corte transversal realizado en 228 personas viviendo con HIV/Sida en un municipio del estado de Sao Paulo, durante 2007 y 2008. Los objetivos fueron investigar la intensidad de los síntomas de depresión en individuos con HIV/Sida atendidos en dos unidades de referencia en Ribeirao Preto, SP, y comparar la calidad de vida con los diferentes grados de intensidad de los síntomas de depresión en esos individuos, según el género. Los datos fueron recolectados por medio de entrevistas individuales, utilizando el Inventario de Depresión de Beck y HIV/AIDS Targeted Quality of Life (HATQoL). Se detectaron 63 (27,6%) individuos con síntomas de depresión (leve, moderado y grave). Las mujeres presentaron síntomas de intensidad más grave de depresión que los hombres. Individuos con síntomas depresivos presentaron menores puntajes de calidad de vida que individuos con ausencia de esos síntomas, con diferencias estadísticamente significativas entre los valores medios/medianos en la mayoría de los dominios del HATQoL. Los profesionales de la salud deben ofrecer asistencia integral a las personas con HIV/Sida, valorizando los síntomas depresivos. Trata-se de estudo de corte transversal, realizado com amostra composta por 228 pessoas vivendo com HIV/AIDS, em um município paulista, durante 2007 e 2008. Os objetivos foram investigar a intensidade dos sintomas de depressão em indivíduos com HIV/AIDS, atendidos em duas unidades de referência, em Ribeirão Preto, SP, e comparar a qualidade de vida aos diferentes graus de intensidade dos sintomas de depressão nesses indivíduos, segundo o gênero. Os dados foram coletados por meio de entrevistas individuais, utilizando-se o inventário de depressão de Beck e HIV/AIDS Targeted Quality of Life (HATQoL). Detectou-se 63 (27,6%) indivíduos com sintomas de depressão (leve, moderada e grave). As mulheres apresentaram sintomas de intensidade mais grave de depressão do que os homens. Indivíduos com sintomas depressivos apresentaram menores escores de qualidade de vida do que indivíduos com ausência desses sintomas, com diferenças estatisticamente significativas entre os valores médios/medianos, na maioria dos domínios do HATQoL. Profissionais de saúde devem oferecer assistência integral às pessoas com HIV/AIDS, valorizando os sintomas depressivos.